A Critical Review of the Book "Loyalty and Leadership in an Early Islamic Society" and Its Translations - Parvin Turkemani Azar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Islamic Society in the 3rd and 4th Hijri centuries is important due to the dominance of the Buyid dynasty, Iranian and Shiite rulers in the Sunni Abbasid caliphate system, so this matter has received the consideration of Iranian scholars, Orientalists, and Islamologists. The research and compilation about this period of history requires the accurate recognition of the Islamic society, Iranian society as well as the views of Sunnis and Shiites. For this reason, the Mottahedeh’s book, which takes approaches about the two components of loyalty and leadership, emphasizing the Buyid, deserves translation and critique. The present critique pertains to the content of the book in the original language. Since the translation of the book is important in the proper transmission of the concepts of history, culture, and the correction of the deficiencies in the original text, it evaluates two existing translations of the book by matching them with the original text as well as adapting the two translation texts. Result shows that lack of proper understanding about the Islamic society, the Iranian customs and culture, and the Buyid encountered problems in the text, despite the innovation and creativity in choosing social discussions. Although the translators of the first translation have not provided enough explanations to address the deficiencies of the content of the book, due to their consistency with the scientific expertise of the author, they have been able to provide more a reliable translation.